Analysis Vibrio Sp. Bacteria from Sipetang (Pharella acutidens) in Mangrove Forest Area Marine Station University Of Riau, Dumai - Saputra, Eka; Yoswaty, Dessy; Tanjung, Afrizal (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
This research was conducted in Februari 2016 in mangrove forest area the Marine Station University of Riau, Dumai. The aim of study was to find out the distribution of bacteria Vibrio sp. from Sipetang which sampled from mangrove forest area the Marine Station University of Riau, Dumai. Determination of sampling point is done by using purposive sampling methods. Sampling points was set into three sampling points. The results of this research was the bacteria vibrio found in sipetang and sediment, therefore bacteria vibrio morphological and biochemical test. Distribution of vibrio bacteria were highest in sampling points III (1,154 x 109), while the lowest was in the sampling point II (5,25 x 105). Vibrio sp. bacteria contained in sipetang and sediment in mangrove forest areas in riau university Marine Station University of Riau, dumai, bacteria in this region might be Vibrio cholerae and Vibrio parahaemolyticus. Â Keywords: Sipetang, Bacteria, Vibrio sp., Mangrove, Dumai.